Pelvic floor muscle function and urinary incontinence in the female athlete. Issue 4 (2nd October 2017) - Casey, Ellen K.; Temme, Kate
ABSTRACT: Urinary incontinence, defined as involuntary leakage of urine, is often considered a disorder of post-partum and post-menopausal women. However, this disorder is not exclusive to older women, as recent research has demonstrated a high prevalence of urinary incontinence among young, nulliparous female athletes. In fact, females participating in repetitive, high-impact sports are at the highest risk for urinary incontinence. In these athletes, the absence of sufficient pelvic floor strength and coordination to withstand sport related increases in intra-abdominal pressure results in physical activity related urinary incontinence, and may be a predictor of urinary incontinence in later adulthood. Pelvic floor dysfunction and urinary incontinence in this population is under-reported and consequently under-diagnosed and under-treated. Therefore, the prevalence is higher than one might expect, and the effects can include decreased performance, change in sport and avoidance of physical activity all together. This manuscript highlights the prevalence of pelvic floor dysfunction and outlines its pathophysiology, diagnosis, treatment, and rehabilitation. We discuss how greater recognition of this disorder by health care providers and routinely querying active females is a critical step in addressing this issue. Identification, education and appropriate rehabilitation can positively affect outcomes in regards to urinary incontinence symptoms and maintain physical activity participation in these athletes.